Analisis Motivasi Pendonor Darah di PMI Kabupaten Sleman Yogyakarta - Hartalina Mufidah; Handriani Kristanti; Eva Runi Khristiani (Poltekkes Kemenkes Mataram, 2022)
Blood donation is an essential element in blood transfusion. The Indonesian Red Cross of Sleman Regency (PMI) is one of the Blood Donor Units in the Province of D.I. Yogyakarta, but only 1% of the population in Sleman became blood donors. Blood donation motivation is closely related with knowledge, attitude, and behavior. This study aims to determine the motivational factors for blood donation at PMI Sleman Regency. This research used a cross-sectional study design which was carried out at PMI Sleman in January-December 2021. The sample of this study was 100 respondents who were determined using the accidental sampling technique. Analysis of research data was carried out univariate and bivariate with Fisher's exact test. The results of this study indicate that age (p-value 0.901>0.05), gender (p-value 0.597>0.05), education (p-value 0.914>0.05), occupation (p-value 0.797>0.05), knowledge (p-value 0.097>0.05), and attitudes (p-value 0.393>0.05) didn’t have relationship with blood donor motivation, but there was relationship between behavior and motivation about blood donation with p-value 0.009<0 ,05. Based on the results of this study, it can be concluded that knowledge, attitudes, and behavior are motivational factors for blood donors, but behavior is a significant factor in blood donor motivation in PMI, Sleman Regency, Yogyakarta. Increasing routine blood donation activities and educating the public about the value of blood donation could create good behavior for voluntary blood donors